Innovaciones en la gestión y calidad de los revestimientos refractarios en la Compañía Sideŕurgica Nacional (Brasil) - Justus, S. M. [UNESP]; Andrade, R. M. [UNESP]; Nascimento Silva, S.; Marques, O. R.; Rivas Mercury, J. M.; Cava, S. [UNESP]; Soledade, L. E B [UNESP]; Santos, I. M G [UNESP]; Baldo, J. B.; Paskocimas, C. A. [UNESP]; Leite, E. R. [UNESP]; Varela, José Arana [UNESP]; et al. (Elsevier, 2002)
The work describes actions carried out in colaboration among the National Steel Company - (CSN)-Brazil and the Interdisciplinary Laboratory of Electrochemistry and Ceramic - LIEC of the Federal University of Sao Carlos Brazil (UFSCar-Brazil), in the area of I&D, for integral management and improvement of the quality and performance of the refractory linings in the sintering areas, blast furnace, hot air pipe lines transferency to the blast furnace, pig-iron ladles, running channels, blast furnaces hearths, torpedo car, etc., as well as, the economic impact generated by the installation of the adopted measures.
Innovation in the management and improvement of the quality in the refractory linings of the National Steel Company - (CSN)-Brazil
Keywords: Brazilian Siderurgy; Management; Quality; Refractories Lining